ORAL HISTORY AND ARCHIVES ON THE PROBLEM OF DOCUMENTING TECHNOLOGIES (Scientific journal of the Fergana State University, 2023)
This article was prepared by the author on the basis of many years’ research in the field of theory and practice of oral history, was tested in the field research and stationary work, as well as at various conferences, webinars and scientific and educational seminars in the Higher Education system.The main attention is given in the article to the analysis of the process of archiving, as a mandatory aspect of oral history research. The article focuses on content issues in the archives with sufficient background information to provide context for the interview.The author comes to the conclusion about the uniqueness of the oral history archive, their difference from classical archives, not only in terms of analyzing the voice and emotional background of the informant's story, but also in identifying the "human dimension" and regional specifics of memory about various historical periods of the country, as well as the phenomenon personal participation of the researcher in the formation of archival funds of oral history materials.